Analysis of Innovation’s Corporate Entrepreneurship on SMEs - Leonard, Rivaldo; Yuwono, Wisnu; Saputra, Suyono (Forum Kerjasama Pendidikan Tinggi, 2025)
This study aims to determine the effect of technological changes, organizational culture, and government policies and support on corporate entrepreneurial innovation in SMEs, through the mediation of strategic orientation, human capital, and policies and procedures, targeting SMEs located in Batam City. The method used is a quantitative approach, using statistical testing and hypothesis testing through SMARTPLS software, to conduct inner and outer modeling tests. Based on the research conducted, it can be concluded that technological changes, organizational culture, and government policies and support show a significant influence on the formation of strategic orientation and policies and procedures. Organizational culture is able to show a significant influence on human capital, but technological changes and policies and government support do not show a significant influence on the formation of human capital. In addition, this study also proves that strategic orientation and policies and government support show a significant influence on innovation and corporate entrepreneurship of SMEs in Batam City. Meanwhile, human capital does not significantly affect innovation and corporate entrepreneurship of SMEs in Batam City.